JURIDICAL ANALYSIS BETWEEN LIFE INSURANCE COMPANY AND INDEPENDENT MARKETING OFFICE IN DISTRICT COURT DECISION NUMBER: 661/PDT.G/2021/PN.JKT.SEL - Puspita, Bunga Putri; Razak, M. Abdul (jfpublisher, 2023)
We need a financial service organisation that assists in managing and planning one’s finances in order to achieve a prosperous life in society. In addition, a fair and transparent agreement is needed in arranging insurance. All companies in the financial services sector including insurance companies must be supervised by Financial Services Authority (OJK) as stipulated in Law No. 40/2014 on insurance. It is conducted to prevent potential fraud that can endanger customers. Therefore this research is conducted to find out and analyse about cooperation agreement procedure between life insurance company and independent marketing office especially the case on District Court Decision Number: 661/Pdt.G/2021/Pn.Jkt.Sel. The type of research used is normative combined with a statutory and case study approach. The research results indicate that an insurance agreement must fulfil the requirements in accordance with Article 1320 BW and the mandatory provisions of the Criminal Code Articles 250-251. Independent marketing offices that cooperate with insurance companies must always be aware in conducting agreements to prevent unwanted force majeure in the future. The legal effect of force majeure is that the defendant cannot fulfil its obligations in the engagement, but the South Jakarta District Court has determined that the defendant must pay costs, penalties and interest.